Can risk aversion explain schooling attainments? Evidence from Italy - Christian Belzil; Marco Leonardi (Institute for the Study of Labor (IZA), 2006)
Using unique Italian panel data, in which individual differences in behavior toward risk are measured from answers to a lottery question, we investigate if (and to what extent) risk aversion can explain differences in schooling attainments. We formulate the schooling decision process as a reduced-form dynamic discrete choice. The model is estimated with a degree of flexibility virtually compatible with semi-parametric likelihood techniques. We analyze how grade transition from one level to the next varies with preference heterogeneity (risk aversion), parental human capital, socioeconomic variables and persistent unobserved (to the econometrician) heterogeneity. We present evidence that schooling continuation probabilities decrease with risk aversion at low grade levels, but increase with risk aversion at the time when the decision to enter higher education is made. However, differences in attitudes toward risk account for a modest portion of the probability of entering higher education. Differences in parental human capital and ability(ies) are much more important.
Keywords: J24; 330; risk aversion; education; human capital; dynamic discrete choices